2020
DOI: 10.1016/j.ijid.2020.08.082
|View full text |Cite
|
Sign up to set email alerts
|

Predominant secondary dengue infection among Vietnamese adults mostly without warning signs and severe disease

Abstract: Background: The morbidity in dengue fever is dependent on the dengue virus (DENV) serotypes, the patient age, predisposing immunogenic markers and the frequency of primary and secondary infections. This study aims to distinguish acute primary from secondary dengue infections of Vietnamese adults and to assess the association of viremia and anti-dengue immunoglobulin levels with clinical outcomes. Study design: Viral RNA, dengue serotypes and levels of anti-dengue IgM and IgG of hospitalized adult cases were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…A cohort study of hospitalized adult patients in northern Vietnam during 2016–2019 reported that dengue with warning signs in primary infection were found in 33% of patients in the 2017–2018 season and in 17% in the 2018–2019 season. Dengue with warning signs was found more often in secondary infection, at 40% in the 2017–2018 season and at 21% in the 2018–2019 season, while there were few cases of severe dengue [ 21 ]. DENV-1 was reported as the primary serotype responsible for the 2017 epidemic [ 7 , 22 ], whereas DENV-2 was the predominant serotype in the 2019–2020 season.…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study of hospitalized adult patients in northern Vietnam during 2016–2019 reported that dengue with warning signs in primary infection were found in 33% of patients in the 2017–2018 season and in 17% in the 2018–2019 season. Dengue with warning signs was found more often in secondary infection, at 40% in the 2017–2018 season and at 21% in the 2018–2019 season, while there were few cases of severe dengue [ 21 ]. DENV-1 was reported as the primary serotype responsible for the 2017 epidemic [ 7 , 22 ], whereas DENV-2 was the predominant serotype in the 2019–2020 season.…”
Section: Discussionmentioning
confidence: 99%
“…1 H, 13 C, DEPT, HSQC, HMBC, COSY, NOESY), which were reported in-detail in our preceding publication [25] The composition includes ursolic acid (1), esculentic acid (2), 2-O-trans-p-coumaroylalphitolic acid (3), a mixture of (6S,7Z,9S)-6,9-dihydroxy-7-megastigmen-3-one ( 4) and (À )-boscialin ( 5), astragalin (6), tiliroside ( 7), 2phyten-1-ol ( 8), 4-[3'-(hydroxymethyl)oxiran-2'-yl]-2,6dimethoxyphenol (9) (Figure 4). The chemical constituents are triterpenoids, flavonoids, phenol, and megastimanes, which are known highly active against dengue virus.…”
Section: Discussion On Chemical and Anti-dengue Activitymentioning
confidence: 99%
“…In Vietnam, dengue fever is an annual disease with the serious outbreaks during the rainy season (between August and December), emerged with the presence of all four serotypes DENV‐1, ‐2, ‐3, and ‐4. A study in epidemiology on the hospitalised dengue fever cases in Vietnam between October 2016 and March 2019 indicated that the secondary infection with DENV‐1 and DENV‐2 serotypes are predominant (DENV‐1: 60–65 %; DENV‐2: 22–26 %) [6] . Also, the dengue infections in both areas, the South and the North of Vietnam, register some different characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein is present in the serum of patients in the early stage of infection [9]. Therefore, NS1 protein has been used as a diagnostic marker of dengue virus infection [10,11]. The NS1 protein has been included in immunological tests such as enzymelinked immunosorbent assay (ELISA) and lateral flow immunoassay test strip (LFA).…”
Section: Introductionmentioning
confidence: 99%